2011
DOI: 10.3390/toxins3121569
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxins Produced by Fungi Associated with Grapevine Trunk Diseases

Abstract: Up to 60 species of fungi in the Botryosphaeriaceae family, genera Cadophora, Cryptovalsa, Cylindrocarpon, Diatrype, Diatrypella, Eutypa, Eutypella, Fomitiporella, Fomitiporia, Inocutis, Phaeoacremonium and Phaeomoniella have been isolated from decline-affected grapevines all around the World. The main grapevine trunk diseases of mature vines are Eutypa dieback, the esca complex and cankers caused by the Botryospheriaceae, while in young vines the main diseases are Petri and black foot diseases. To understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
184
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 156 publications
(189 citation statements)
references
References 102 publications
5
184
0
Order By: Relevance
“…These fungi produce a variety of compounds in their hosts as well as in artificial media, and some of these molecules have been characterised (for review, see Andolfi et al 2011). The effects of fungal extracellular compounds on defence gene expression in V. vinifera can be evaluated under different conditions: in the field, in greenhouses or in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These fungi produce a variety of compounds in their hosts as well as in artificial media, and some of these molecules have been characterised (for review, see Andolfi et al 2011). The effects of fungal extracellular compounds on defence gene expression in V. vinifera can be evaluated under different conditions: in the field, in greenhouses or in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the toxicity, we decided to evaluate whether mellein which is produced by these fungi and is described as both a characteristic toxin of Botryosphaeriaceae and a possible diagnostic marker for diseased grapevines (Andolfi et al 2011), was responsible for the reactions observed in calli. Mellein was first reported as a toxin produced by D. seriata.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations